2016
DOI: 10.1016/j.elstat.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and interpretation of photo-stimulated discharge spectrum for polypropylene films under different electric and geometrical conditions

Abstract: show that the occurrence of photoemissions from electrode or polymer at wavelengths less than about 260 nm is possible, depending on the polarity and amplitude of applied voltage. The photocurrent spectra for samples with circular electrodes characterize two charge de-trapping peaks and the peak at 273 nm is also partially contributed by the photoelectrons from electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The metal nature of the electrodes, through the work function, directly influences the PSD response. Ma et al [153], studying the photo-stimulated discharge spectrum of polypropylene films, showed that the position of the peak is shifted to the longer wavelengths when Au (work function of 5.1 eV) is replaced by Al (work function of 4.28 eV) for the electrode facing to the light irradiation. The thickness and geometry of electrodes are also important parameters.…”
Section: The Experimental Parameters Linked To the Sample And Electrodesmentioning
confidence: 99%
“…The metal nature of the electrodes, through the work function, directly influences the PSD response. Ma et al [153], studying the photo-stimulated discharge spectrum of polypropylene films, showed that the position of the peak is shifted to the longer wavelengths when Au (work function of 5.1 eV) is replaced by Al (work function of 4.28 eV) for the electrode facing to the light irradiation. The thickness and geometry of electrodes are also important parameters.…”
Section: The Experimental Parameters Linked To the Sample And Electrodesmentioning
confidence: 99%
“…Concerning the double PSD peak located in the 260-200 nm range, optical detrapping is not excluded, but other phenomena like photo-emission from the metallic electrode can be at play. Actually, by changing the metal nature of the front electrode, Ma et al [4] have shown a direct correlation between the work function of the metal and the cut-off wavelength of the peak observed in the 200-300 nm range for BoPP. The authors suggest that this peak results from electron emission via photoelectric effect from the front finger electrode when a local strong electric field exists.…”
Section: A Psd/limm Spectramentioning
confidence: 99%
“…Another point to consider concerns the fingered electrode used as front electrode. It can first induce a field enhancement du to edge effect and as a consequence, charge injection and trapping at the edge of the fingers of the top electrode can be increased [4]. Besides, the fingered electrode plays a great role when considering the area (or volume) of the polymer material probed when LIMM and PSD are performed.…”
Section: A Psd/limm Spectramentioning
confidence: 99%
See 2 more Smart Citations